Contribution of School Canteen's Snacks to The Iron Fulfillment in Malang High Schools - Adelya Kurniawati; Titis Sari Kusuma; Wahyu Winariyanti; Dedy Iskandar Putra (Indonesian Journal of Human Nutrition, 2022)
Inadequate dietary iron, impaired iron absorption, bleeding, or loss of body iron in the urine may cause anemia. The prevalence of anemia due to iron (Fe) deficiency in Indonesia reaches 22.7% in females and 12.4% in males. Indonesian students spent 7-8 hours/day, mainly the iron daily intake influenced by school canteen snacks. This study aimed to determine the contribution of Fe content in canteen snacks in high schools in Malang. This research was an analytic observational study using a cross-sectional design with the AAS (Atomic Absorption Spectrometry) method as a quantitative iron analysis technique. Food samples were selected purposively according to the inclusion criteria from 10 high schools consisting of junior high and senior high school groups. The snack samples studied were fried chicken, fried Tempe, and noodles. The average Fe content in snacks was analyzed using the independent T-test in the junior and senior high school groups. The iron content in fried Tempe and noodle showed a significant difference with p> 0.05, while the iron content in fried chicken in the two school groups did not show different results. However, the percentage contribution of Fe to the Nutrition Adequacy Rate (RDA) is still minimal, with the most significant contribution coming from noodles, reaching 17.85% in the male group.